Temozolomide Therapy for Aggressive Pituitary Tumors: Results in a Small Series of Patients from Argentina - Oscar D. Bruno; Lea Juárez-Allen; Silvia B. Christiansen; Marcos Manavela; Karina Danilowicz; Carlos Vigovich; Reynaldo M. Gómez (International Journal of Endocrinology)
We evaluated results of temozolomide (TMZ) therapy in six patients, aged 34–78 years, presenting aggressive pituitary tumors. In all the patients tested O6-methylguanine-DNA methyltransferase (MGMT) immunoexpression in surgical specimens was absent. Patients received temozolomide 140–320 mg/day for 5 days monthly for at least 3 months. In two patients minimum time for evaluation could not be reached because of death in a 76-year-old man with a malignant prolactinoma and of severe neutro-thrombopenia in a 47-year-old woman with nonfunctioning pituitary adenoma. In two patients (a 34-year-old acromegalic woman and a 39-year-old woman with Nelson’s syndrome) no response was observed after 4 and 6 months, respectively, and the treatment was stopped. Conversely, two 52- and 42-year-old women with Cushing’s disease had long-term total clinical and radiological remissions which persisted after stopping temozolomide. We conclude that TMZ therapy may be of variable efficacy depending on—until now—incompletely understood factors. Cooperative work on a greater number of cases of aggressive pituitary tumors should be crucial to establish the indications, doses, and duration of temozolomide administration.